2023
DOI: 10.1590/2447-536x.v29i1.2528
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dormancy breaking methods on germination of Cercis siliquastrum and Spartium junceum and seedling growth

Abstract: Seed dormancy is a mechanism of long survival that is ecologically important for seed propagation and dispersal and the expansion of plant populations. The impermeability of the seed coat in the Fabaceae family is due to a layer of sclerotic cells. Two experiments were conducted to investigate the effect of different seed treatment on germination parameters and seedling growth in Cercis siliquastrum and Spartium junceum. Experimental treatments comprised of chemical and thermal scarification treatment consisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
1
0
1
Order By: Relevance
“…Yuniarti and Djaman (2015) reported that H2SO4 could increase imbibition rate by releasing hydrophilic colloids, removing the waxy layer on the seed coat and making it permeable to gas and water. H2SO4 treatment will damage the cell lining of the macrosclereid lumens resulting in water imbibition and the release of simple sugars for protein synthesis, which promotes germination (Taghizadeh and Sajadi, 2023).…”
Section: Dormancy Mechanismmentioning
confidence: 99%
“…Yuniarti and Djaman (2015) reported that H2SO4 could increase imbibition rate by releasing hydrophilic colloids, removing the waxy layer on the seed coat and making it permeable to gas and water. H2SO4 treatment will damage the cell lining of the macrosclereid lumens resulting in water imbibition and the release of simple sugars for protein synthesis, which promotes germination (Taghizadeh and Sajadi, 2023).…”
Section: Dormancy Mechanismmentioning
confidence: 99%
“…Diferentes métodos foram testados para superar a dormência, como os tratamentos químicos (ácido sulfúrico) e a água fervente, que se mostraram eficazes para superar a dormência de sementes em várias espécies (TAGHIZADEH, 2023;LIYANAGE et al, 2022), além da escarificação mecânica e variação de temperatura e luz. Estudos têm demonstrado que diferentes tratamentos têm efeitos variados na porcentagem de germinação e nos parâmetros de crescimento das plântulas (MURTIĆ, 2023; NAUTIYAL; SIVASUBRAMANIAM; DADLANI 2023).…”
Section: Introductionunclassified